CDKN2A deletion in pediatric versus adult glioblastomas and predictive value of p16 immunohistochemistry. Issue 4 (14th January 2013) - Purkait, Suvendu; Jha, Prerana; Sharma, Mehar Chand; Suri, Vaishali; Sharma, Manish; Kale, Shashank Sharad; Sarkar, Chitra
Abstract : Cell cycle regulator genes are major target of mutation in many human malignancies including glioblastomas (GBMs). CDKN2A is one such tumor suppressor gene which encodes p16INK4a protein and serves as an inhibitor of cell cycle progression. Very few studies are available regarding the association of CDKN2A deletion with p16 protein expression in GBMs. There is limited data on the frequency of CDKN2A deletion in different age groups. The aim of the present study was to analyze the frequency of CDKN2A gene deletions in GBM and correlate CDKN2A deletional status with (i) age of the patient (ii) p16 protein expression and (iii) other genetic alterations, namely EGFR amplification and TP53 mutation. A combined retrospective and prospective study was conducted. Sixty seven cases were included. The patients were grouped into pediatric (≤18 years), young adults (19‐40 years) and older adults (>40 years). CDKN2A and EGFR status were assessed by Fluorescence in situ Hybridization.TP53 mutation was analyzed by PCR based method. p16 expression was assessed using immunohistochemistry. CDKN2A deletion was noted in 40.3% cases of GBM with majority being homozygous deletion (74%). It was commoner in primary GBMs (65.8%) and cases with EGFR amplification (50%). A variable frequency of CDKN2A was observed in older adults (42.3%), young adults (44%), and pediatric patients (31.25%). The difference however was not statistically significant. There was statistically significant association between CDKN2A deletion and p16 immunonegativity with a high negative predictive value of immunohistochemistry.